PHP Web Services / APIs for the Modern Web - Mitchell Lorna Jane (O'Reilly Media, 2016)
This book includes new tools and features that reflect PHD updates and changes on the web. HTTP, HTTP Verbs, Headers, Cookies, JSON, XML, PPC and SOAP Services, REST, Webbooks, HTTP Tools, Maintainable Web Services, Making Service Design Decisions, Building a Robust Service, Publishing Your API, A Guide to Common Status Codes, Common HTTP Headers, Index.